Subjective theories of illness in fibroid and endometriosis patients: Similarities, differences, and influencing factors. Issue 2 (June 2022) - Münch, Friederike; Ebert, Andreas D; Mechsner, Sylvia; Richter, Rolf; David, Matthias
Introduction: The aim of this study was to compare the subjective theories of illness in patients with fibroids and patients with endometriosis, and to identify potential factors influencing them. Methodology: Participating patients were recruited via three specialized centers for fibroids and endometriosis. To assess their subjective theories concerning the cause of their illness, we used a questionnaire based on the revised Illness Perceptions Questionnaire (IPQ-R). We also gathered and evaluated data relating to sociodemographic factors and psychological distress or possible anxieties using the Kessler Psychological Distress Scale (K10) and the Generalised Anxiety Disorder Assessment (GAD-7). Results: We were able to analyze data from 201 patients with fibroids and 212 patients with endometriosis. About 94.4% of the patients had one or more subjective theories concerning the cause of their illness. Both groups perceived "stress or worry" to be the most probable cause of their illness. Compared to endometriosis patients, patients with fibroids were more likely to assume "aging" and "heredity" as the cause of their illness. Endometriosis patients, on the other hand, were more likely to choose theories pertaining to the "environmental influences and immune system" category. The patients' age, formal education, and conspicuous score values in the K10 or GAD-7 questionnaire proved to be important factors influencing their beliefs about the cause of illness. Conclusion: Patients perceive stress and psychological strain as possible causes for their illness. It might be beneficial to take this information into account in conversations between doctors and patients and when drawing up psychosomatic-gynecological treatment plans.